2021
DOI: 10.3389/fmicb.2021.731786
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Marine Diatom-Dinoflagellate Competition to Multiple Environmental Drivers: Abundance, Elemental, and Biochemical Aspects

Abstract: Ocean-related global change has strongly affected the competition between key marine phytoplankton groups, such as diatoms and dinoflagellates, especially with the deleterious consequency of the increasing occurrence of harmful algal blooms. The dominance of diatoms generally shifts toward that of dinoflagellates in response to increasing temperature and reduced nutrient availability; however, contradictory findings have also been observed in certain sea areas. A key challenge in ecology and biogeochemistry is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…Regarding the phytoplankton community, at Station 2 dinoflagellate abundance was on average 1.5 times higher than at control stations, while low concentrations of diatoms were found, confirming that several environmental factors-in addition to T and nutrient availability-may influence the diatom-dinoflagellate patterns and succession. The prevalence of diatoms independently on T and N:P supply ratios and a switchback towards the dinoflagellates' dominance at high T and nutrient concentrations have recently been observed [53].…”
Section: Microbial Response To Freshwater Inputsmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the phytoplankton community, at Station 2 dinoflagellate abundance was on average 1.5 times higher than at control stations, while low concentrations of diatoms were found, confirming that several environmental factors-in addition to T and nutrient availability-may influence the diatom-dinoflagellate patterns and succession. The prevalence of diatoms independently on T and N:P supply ratios and a switchback towards the dinoflagellates' dominance at high T and nutrient concentrations have recently been observed [53].…”
Section: Microbial Response To Freshwater Inputsmentioning
confidence: 97%
“…Phytoplankton communities are known to influence water turbidity and the dissolved oxygen content, and, because of their responsiveness to nutrient or S changes in terms of their structure and distribution, they are regarded as sensitive proxies for several ecosystem processes [79,80]. Through symbiosis or resource competition, phytoplankton communities also interact with other planktonic components; the associations/interactions between microbial community members allow us to understand the effect of changing environmental conditions on ecosystem functioning [53,81]. Within the phytoplanktonic community inhabiting the Syracuse bay, dinoflagellates prevailed throughout the study period and, occasionally, diatoms in summer at marine stations; moreover, the negative association found between these two taxa could be explained by the high optimal N/P ratio of dinoflagellates in contrast to the low optimal N/P ratio that favors the growth of diatoms, by the different mechanisms of nutrient uptake [81].…”
Section: Biogeochemical Implications Of Microbial Activities and Related Stoichiometric Ratiosmentioning
confidence: 99%
“…Finally, the negative relationship with dissolved phosphorus complies with Li et al (2015) who showed that P. minimum blooms are associated with low phosphate concentrations in the Chesapeake Bay. Bi et al (2021) also found a negative relationship between the ratio of particulate organic nitrogen to particulate organic phosphorus and diatom to P. minimum ratio.…”
Section: Importance Of Biogeochemistry and Hydrodynamicsmentioning
confidence: 76%
“…The level of eutrophication and resulting hypoxia reflect relative inputs of N, P, and silica (Si) over space and time (Justić et al, 1995; Turner et al, 2006). High N and Si inputs favor the production of large, rapidly sinking phytoplankton species, while higher relative P inputs promote small, slower sinking dinoflagellate communities (Bi et al, 2021; Glibert et al, 2011; Guo et al, 2014). However, how the decreasing N:P loading ratio would impact harmful algal blooms is still unclear and calls for more studies.…”
Section: Resultsmentioning
confidence: 99%